APPRAISAL OF ENGLISH LANGUAGE TEACHERS’ ROLE IN PAKISTANI COLLEGES FROM DIRECT INFLUENCE PERSPECTIVE - Ali Asghar; Dr. Muhammad Akbar Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
This study aims at investigating the role of English language teachers in the learning process of EFL students in Pakistani public sector colleges. It is the responsibility of the English language teachers to ensure students’ proficiency in reading and writing skills at graduation level according to the prescribed syllabi. For this purpose, it is essential that the teacher should allocate equal time to all the activities in the classroom. The role of English language teacher is of pivotal nature for learning process and students’ linguistic proficiency depends on him. Therefore, the present research has been conducted to ascertain the role of English language teacher in EFL classes arranged in randomly selected Pakistani government colleges of Lahore, Pakistan. Flander’s (1970) Model of Interactive Analysis Category System – based on direct observation – has been selected as a tool for collecting data. The analysis was done by mixed methods keeping in view the outlines provided by McCarthy (1991). The researchers have found that the teachers in public sector male colleges of Lahore are not performing their duties up to the mark. They do not engage students in different activities adjunctive for the learning process. They do not attempt to boost confidence among students. They prefer to stick with direct influence, i.e. lecturing, asking questions, imposing their authoritative attitude on the students by their knowledge, scolding the students, and these factors result in the form of silence on the part of learners. Hence, to fulfill the real purpose of education, the direct influence on the part of teachers has to be controlled and indirect influence has to be increased.